Bobot Daging Dada dan Karkas Puyuh setelah Penyembelihan, Pembekuan, dan Thawing - Syahrizal Nasution; Kusmayadi Suradi; Jajang Gumilar (Unpad Press, 2021)
Weight is one of the important variables that need to be considered in producing carcass and meat. This study aimed to determine the weight of live quail, fresh carcass, frozen carcass, quail carcass and breast meat after thawing. The weighing was done before the slaughtering process, after becoming fresh carcass, after freezing, after thawing, and after separating the quail breast meat. Thawing loss and the total loss was measured to know the loss percentage of the weight of quail carcass. Weighing produces the weight of live quail is 248,50 ± 20,72 grams, fresh carcass weight after slaughtering is 167,50 ± 17,06 grams, frozen carcass weight after freezing is 163,85 ± 17,06 grams. Carcass weight after thawing sequentially at 6-8°C (24 hours), 24-26°C (6 hours), 22-23°C (2,5 hours), and 55°C (1 hour) amounting to 158,20 ± 19,87 grams, 165,60 ± 19,40 grams, 167,80 ± 12,40 grams, 157,20 ± 19,84 grams, and quail meat sequentially 50,20 ± 6,26 grams, 52,60 ± 6,31 grams, 53,20 ± 3,70 grams, 49,80 ± 6,22 grams. The weight percentage of carcass inversely proportional to thawing loss and total loss produced. The results showed that carcass weight decreased after cutting, freezing, and thawing. The heaviest weight of quail meat and carcass and the lowest total loss of carcass were produced from thawing at a temperature of 22-23°C.